2000
DOI: 10.1007/bf02434865
|View full text |Cite
|
Sign up to set email alerts
|

Liver resistance to CCl4-induced injury after stimulation of macrophages with various preparations

Abstract: Acute toxic hepatitis in male Wistar rats was produced by single injection of 40% CCl(4) (0.2 ml per 100 g body weight in oil). Pretreatment with various immunostimulators (bacterial polysaccharides prodigiozan and salmozan; yeast polysaccharides zymosan, peptidoglycan, and mannan; and hydrolytic enzyme egg lysozyme) produced a hepatoprotective effect correlating which the stimulatory influence on macrophages and increasing in the following order: mannan

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Activated resident Kupffer cells and the neutrophils recruited at the site of parenchymal liver injury are considered as the primary culprits in damaging surrounding healthy cells as the result of nonspecific action (Laskin and Pendino, 1995; Luster et al, 2001). However, recent evidence suggests that the contribution of the inflammatory cells does not or is not sufficient to mediate progression of injury (Ju et al, 2002; Kutina and Zubakhin, 2000; Lawson et al, 2002). The second leading theory regarding progression of injury is production of free radicals and oxidative stress, and subsequent lipid peroxidation that propagates injury (Kellogg and Fridovich, 1975; Mylonas and Kouretas, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Activated resident Kupffer cells and the neutrophils recruited at the site of parenchymal liver injury are considered as the primary culprits in damaging surrounding healthy cells as the result of nonspecific action (Laskin and Pendino, 1995; Luster et al, 2001). However, recent evidence suggests that the contribution of the inflammatory cells does not or is not sufficient to mediate progression of injury (Ju et al, 2002; Kutina and Zubakhin, 2000; Lawson et al, 2002). The second leading theory regarding progression of injury is production of free radicals and oxidative stress, and subsequent lipid peroxidation that propagates injury (Kellogg and Fridovich, 1975; Mylonas and Kouretas, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Hypolipemic and associated anti-atherosclerosis effects of β-glucan have been previously investigated ( 16 , 17 ), with evidence demonstrating the favorable effects of β-glucan on the hepatopathies ( 18 , 19 ). However, the direct effects of β-glucan on hyperlipemic liver damage, and the effects on hypolipemia and associated anti-atherosclerosis using the β-glucan originating from Aureobasidium , have not yet been determined.…”
Section: Discussionmentioning
confidence: 99%
“…Previous clinical and animal studies have used concentrated β-glucan preparations from oats and barley and have demonstrated strong hypolipemic and associated anti-atherosclerosis effects on hypercholesterolemic hamsters ( 16 , 17 ). Although certain studies have demonstrated evidence of the direct effects of β-glucan on hepatopathies ( 18 , 19 ), the direct effects of β-glucan on hyperlipemic liver damage are seldom. In addition, the effects of the β-glucan originating from Aureobasidium on hypolipemia and associated anti-atherosclerosis have not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…However, in addition to bacteriolytic activity, lysozyme affects many biochemical and physiological processes in the body. So, it increases the chemotaxis of leukocytes [1], stimulates the lymphocytic system of specific immunity [5], and has hepatoprotective and mucosoprotective effects [6,7].…”
Section: Introductionmentioning
confidence: 99%